Water and wastewater treatment : a guide for the nonengineering professional - Drinan, Joanne E.; Spellman, Frank R. (Florida, United States : CRC Press, 2013)
Designed to meet the information needs of professionals without an engineering background, this book describes and explains in simple, non-mathematical terms the unit processes used to treat both drinking water and wastewater. The text presents each unit process, states what function(s) it performs, illustrates what equipment it uses, and explains its role in the process of purifying or cleaning water. Now featuring summary sections, each chapter in this second edition has been fully updated and revised to present the latest regulatory and technological advancements as well as new drinking and wastewater regulatory requirements
IntroductionCurrent Issues in Water and Wastewater Treatment OperationsBasics of Water TreatmentWater Regulations, Parameters, and CharacteristicsWater Purification: System OverviewSources, Intake, and ScreeningCoagulation and FlocculationSedimentationFiltrationDisinfectionDistributionBasics of Wastewater TreatmentWastewater Regulations, Parameters, and CharacteristicsWastewater Sources and TypesWastewater Treatment: Basic OverviewCollection SystemsPreliminary TreatmentPrimary SedimentationBiological TreatmentSecondary SedimentationAdvanced TreatmentWastewater DisinfectionDischarge EffluentBasics of Water and Wastewater Solids Treatment and ManagementWater Solids Management: System OverviewWater Solids Treatment and DisposalWastewater Biosolids Management: System OverviewWastewater Biosolids TreatmentWastewater Biosolids DisposalGlossaryIndex
Includes bibliographical references.
Keywords: WATER -- PURIFICATION